Islamic Education Values of Barikan: Javanese Cultural Rituals as A Practice of Islam Nusantara - Saefudin, Ahmad; Pangestuti, Deliavega Nanda; Andriyani, Santi (el Harakah: Jurnal Budaya Islam, 2020)
Religion and culture are two important elements in society that influence each other. Even though both have their respective fundamental values, Islam as a religion with tradition as culture in Nusantara can acculturate and come into direct contact in harmony. The Barikan tradition showed that there is a fairly close relationship between religion and local culture. The tradition, which initially aims to pray for ancestral spirits, has since been considered an obligation by the people of Manyargading Village. Through this tradition, they believe that they will get blessings, peace, security, and get an abundant fortune. The Barikan tradition is a representation of Javanese culture that stores the values of Islamic education. They are the values of faith, worship, community, local Islamic history, morals, and da'wah. Agama dan budaya merupakan dua unsur penting dalam masyarakat yang saling mempengaruhi. Walaupun memiliki nilai fundamental masing-masing, Islam sebagai agama dengan tradisi sebagai budaya di Nusantara, mampu berakulturasi dan bersentuhan secara langsung dengan harmonis. Tradisi Barikan menunjukkan adanya perkawinan antara agama dengan budaya lokal yang cukup erat. Tradisi yang awalnya bertujuan untuk mendoakan arwah leluhur, pada perkembangan selanjutnya sudah dianggap sebagai kewajiban oleh masyarakat Desa Manyargading. Melalui tradisi ini, mereka percaya akan mendapatkan keberkahan, ketenteraman, keamanan, dan memperoleh rejeki yang melimpah. Tradisi Barikan menjadi salah satu representasi budaya Jawa yang menyimpan nilai-nilai pendidikan Islam. Di antaranya ialah nilai aqidah, ibadah, kemasyarakatan, sejarah Islam lokal, moral, dan dakwah.